2008
DOI: 10.1016/j.ajog.2007.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Population trends in cesarean delivery for breech presentation in the United States, 1997-2003

Abstract: Objective-To determine if cesarean delivery for breech has increased in the United States.Study Design-We calculated cesarean rates for term singletons in "breech / malpresentation" from 1997-2003 using National Center for Health Statistics data. We compared rates by sociodemographic groups and state. Multivariable logistic regression models were constructed to see if factors associated with cesarean delivery differed over time.Results-Breech cesarean rates increased overall from 83.8% to 85.1%. There was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 17 publications
1
21
0
3
Order By: Relevance
“…In 2000, the Term Breech Trial (TBT) reported a significant reduction in perinatal morbidity and mortality for breech babies delivered by planned caesarean, estimating an excess mortality of 1% with planned vaginal breech birth, and little alteration in maternal morbidity. Despite subsequent studies questioning the validity of these findings, the TBT led to a substantial rise in elective caesarean numbers for breech presentation worldwide . Nevertheless, subsequent analyses have suggested that the risk of planned breech birth is lower, and follow‐up data from the TBT revealed no reduction in the risk of death or neurodevelopmental delay in children at 2 years of age delivered by caesarean .…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, the Term Breech Trial (TBT) reported a significant reduction in perinatal morbidity and mortality for breech babies delivered by planned caesarean, estimating an excess mortality of 1% with planned vaginal breech birth, and little alteration in maternal morbidity. Despite subsequent studies questioning the validity of these findings, the TBT led to a substantial rise in elective caesarean numbers for breech presentation worldwide . Nevertheless, subsequent analyses have suggested that the risk of planned breech birth is lower, and follow‐up data from the TBT revealed no reduction in the risk of death or neurodevelopmental delay in children at 2 years of age delivered by caesarean .…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been focussed on the optimal mode of delivery for breech-presenting babies. Following the findings of the Term Breech Trial, of fewer adverse outcomes among those delivered by planned caesarean section than by planned vaginal delivery,2 birth is now more likely to occur by caesarean section 3. Regardless of mode of delivery, there are increased risks of adverse maternal or neonatal outcomes associated with breech presentation 4,5…”
Section: Introductionmentioning
confidence: 99%
“…Breech presentation at term can be a significant contributor to cesarean births; 85% of women with persistent breech presentations at term undergo cesarean birth . In an effort to reduce this potential effect, an opportunity exists to promote techniques to change breech presentation to vertex.…”
Section: Response—to Every Labor Challengementioning
confidence: 99%